IMPROVING LISTENING SKILLS (Лучшие интеллектуальные исследования, 2024)
Listening skills are critical for effective communication and personal development. This article explores strategies to enhance listening skills, including active listening, empathy, and mindfulness. By adopting these practices, individuals can improve their comprehension, relationships, and overall communication abilities.